Understanding the concept of ‘demand’ in policing: a scoping review and resulting implications for demand management - Laufs, Julian (Policing and society, 2021)
As literature around policing and society grows, there is increased use of, and focus upon the concept of police ‘demand’. The concept itself, however, is ill-defined and no consensus exists about how it should be measured. This paper addresses these issues by undertaking a scoping review of literature on the topic, and by exploring how demand has been conceptualised in both academic and practitioner communities. The review reveals that while key interdependencies between police demand and supply are widely discussed, they are often analysed in isolation. To add to the academic discussion of police demand, the paper introduces a comprehensive conceptualisation including the various forms police demand can take and the different manifestations of drivers for police demand. Subsequently, it outlines several approaches that might be levied to increase the effectiveness and efficiency of demand management approaches. These include the consideration of trade-offs that need to be considered. For example, there is a need to balance any resources allocated to deal with proactive demand reduction and that necessary for (reactive) response. Considering the dynamics of police demand and – by necessity – supply through the lens of complex adaptive systems we propose potential ways forward that capitalise on this framing.